SEQUENCE-RELATED AMPLIFIED POLYMORPHISM (SRAP) FOR STUDYING GENETIC DIVERSITY AND POPULATION STRUCTURE OF PLANTS AND OTHER LIVING ORGANISMS: A PROTOCOL - X. Y. Li1; J. Li; Z. J. Zhao; F. Yang; Q. W. Fu; H. S. Liu; D. D. Wang; Y. C. Yang; R. Y. Wang (Journal of Animal and Plant Sciences, 2014)
Genetic variation is widespread in living organisms. The accurate analysis of genetic variation and studies of population structures have significant implications for understanding the genetic traits, population genetics, molecular breeding and disease control programs in plants and animals. Sequence-related amplified polymorphism (SRAP) analysis has been widely used for studying genetic diversity and population structures of living organisms in the last decade. This molecular approach preferentially targets the open reading frame (ORF) regions of the genome with universal primers to screen the mutations across the whole genome, allowing to investigate genetic variations in the genome, and to develop new specific markers for species or population differentiation and molecular breeding. This article briefly outlined the applications of SRAP technique in plants and animals, and detailed described the protocol of this technique. It will make the usage of this approach conveniently and maneuverably, and further expand its applications to a wider range of living organisms.
Keywords: Sequence-Related Amplified Polymorphism (SRAP); Protocol Review; Genetic Diversity; Population Structure